Factors influencing the use of computer-assisted audit techniques in the digital era - Fülöp, Melinda Timea; Ionescu, Constantin Aurelian; Măgdaș, Nicolae; Topor, Dan Ioan (Journal of Business Economics and Management, 2024)
Digitalization is a challenge of the current environment, and the digital transition has extended to the audit profession. It affects the technology used by clients and the pressure on auditors by audit regulations to apply and use computer-assisted audit techniques (CAATs). The results of specialized literature indicate that the application and use of CAATs in auditing practice are limited. Thus, the present research aimed to investigate the factors that could influence the use of CAATs by auditors, based on the Unified Theory of Acceptance and Use of Technology (UTAUT). The empirical investigation consisted of 112 questionnaires that were analyzed by external auditors. The research results indicated a positive influence on the behavioral intention to use CAATs, which was influenced by performance expectations and facilitating conditions. In contrast, effort expectations and social influence did not affect the behavioral intention to use CAATs. We conclude that management should have a greater involvement in encouraging the use and application of CAATs, including supporting the process with the necessary resources. This work augments the knowledge of the factors that influence the behavioral intention to use CAATs among auditors in Romania and can be a useful resource for practitioners.